Novel quinoline photoinitiators for dimethacrylate monomer photopolymerization under UV and blue light - Fernandes Moreno, Vitor [UNESP]; Hori Barboza, Bruno [UNESP]; Michelão Martins, Lucas [UNESP]; Gaglieri, Caroline [UNESP]; Bannach, Gilbert [UNESP]; Batagin-Neto, Augusto [UNESP]; da Silva-Filho, Luiz Carlos [UNESP] (Elsevier, 2024)
Composite resins based on methacrylated monomers are the main materials for dental restorations, however, incomplete polymerization and leaching have been identified as the major problems in this process, highlighting the importance of a search for new photoinitiating materials with improved properties and, therefore, can produce cheaper and stronger polymers with reduced toxicity. In this work, two novel quinoline derivatives were evaluated to obtain dimethacrylate-based polymers. Here we present the synthesis and characterization of a quinoline derivative containing a hydroxyl group and another containing a methacrylate group, as type II photoinitiator materials for UDMA-based resins polymerization. The photoinitiators were analyzed through photolysis (at two distinct wavelengths) and theoretical calculations were performed via a DFT-based approach, to provide a better understanding of the photoexcitation process of quinoline-based photoinitiators. The thermal stability, mass loss rate and glass transition of the generated polymers and the quinoline photoinitiators were analyzed via TG-DTA and DSC. The morphological characteristics of final polymerized compounds were performed with scanning electron microscopy. The water sorption and solubility were also investigated. Our results indicate that hydroxyl-containing quinoline promotes an efficient photopolymerization of UDMA resin precursors under blue light (65.9 %), while methacrylate-containing quinoline presents higher conversions under ultraviolet irradiation (66.3 %). The polymerization of the compounds presented 40 % to 66 % conversion under 60 s, comparable to the camphorquinone standard at the same conditions. The polymer of UDMA with hydroxyl-containing quinoline, showed a slightly higher water sorption than the methacrylate-containing one and both indicate no solubility in water at 37 °C. Overall, the results show that quinoline-based photoinitiators present an efficient photopolymerization of UDMA and produce fluorescent polymers, similarly to commonly used resin materials.
Keywords: Density functional theory; Fluorescent polymers; Photoinitiator; Photopolymerization; Quinoline derivatives